The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1167/iovs.62.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 and Transforming Growth Factor Beta: Commonly Opposing, but Sometimes Supporting, Master Regulators of the Corneal Wound Healing Response to Injury

Abstract: Purpose Interleukin (IL)-1α/IL-1β and transforming growth factor (TGF)β1/TGFβ2 have both been promoted as “master regulators” of the corneal wound healing response due to the large number of processes each regulates after injury or infection. The purpose of this review is to highlight the interactions between these systems in regulating corneal wound healing. Methods We conducted a systematic review of the literature. Results Both regulator p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 154 publications
(367 reference statements)
0
23
0
Order By: Relevance
“…In mouse calvarial osteoblasts, TGFβ abolishes the induction of cyclooxygenase 2 by IL1β ( 67 ). TGFβ and IL1β also antagonistically modulate apoptosis of corneal myoblasts ( 68 ). In trophoblasts, TGFβ and IL1β have inhibitory and stimulatory effects, respectively, on cell invasion ( 32 , 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mouse calvarial osteoblasts, TGFβ abolishes the induction of cyclooxygenase 2 by IL1β ( 67 ). TGFβ and IL1β also antagonistically modulate apoptosis of corneal myoblasts ( 68 ). In trophoblasts, TGFβ and IL1β have inhibitory and stimulatory effects, respectively, on cell invasion ( 32 , 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that the activation of the NLRP3 inflammasome involves an inflammatory response, which is mainly driven by the release of proinflammatory cytokine IL-1β and IL-18. 29 , 30 Coincidentally, IL-1β plays a pivotal role in the pathogenesis of inflammation and fibrosis 31 , 32 ; moreover, it amplifies the effects of other cytokines. 18 In liver diseases, the NLRP3 inflammasome activation indirectly induces liver inflammation and fibrosis in a cytokine-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 alpha released by epithelial or endothelial injury triggers other important functions in corneal fibroblasts. 66 Gene array experiments 67 demonstrated that IL-1 alpha (and tumor necrosis factor-alpha) stimulate the transcription of many chemokines, such as monocyte-derived neutrophil chemotactic factor, chemokine (C–C motif) ligand 2, also called monocyte chemoattractant protein-1, granulocyte colony-stimulating factor, and C-X-C motif chemokine 5 (also called neutrophil-activating peptide or ENA-78), that amplify the effect of IL-1 alpha itself in drawing not only fibrocytes, but other bone marrow-derived cells, such as lymphocytes, neutrophils, and macrophages, into the corneal stroma. IL-1 alpha also upregulates the production of hepatocyte growth factor and keratinocyte growth factor (or fibroblast growth factor-7) 68 , 69 that stimulate epithelial healing by modulating the proliferation, motility, differentiation, and apoptosis of corneal epithelial cells.…”
Section: Contributions Of Corneal Nerves To Transparencymentioning
confidence: 99%